The Impact of the COVID-19 on the Chinese Stock Market and the Role of Investor Sentiment - Liu, Shuyao (2020)
This paper considers five critical events, including three negative and two positive events, during the COVID-19 outbreak from late 2019 to early 2021 and examines their impact on a sample of 1,698 stocks in the China Shenzhen A market. Using an event study approach, the paper finds that the stock market fell significantly on both the negative event date and the subsequent trading day, while the positive events positively impacted the stock market. The paper further considers investor sentiment following the outbreak, constructing sentiment indicators based on individual stock turnover rates and the number of new and cured cases per day of COVID-19, respectively. It also finds that the turnover rate is positively related to abnormal stock market returns, and the sentiment indicators constructed with COVID-19 data are not equally related to abnormal stock market returns in each event. In the industry heterogeneity test, most of the industries except for real estate and other industries were to the adverse shock of event 1, while event 5 had a favourable impact on all sectors. The data and results in this paper are robust for all events except event 2.